Digital Transformation of Administration in Improving Hospital Strategic Competitiveness - Aya Sofia Diaz; Natasya Adinda Putri (JURNAL KESMAS DAN GIZI (JKG), 2026)
Digital transformation in the healthcare sector is a strategic phenomenon that plays a role in reshaping administrative systems and increasing hospital competitiveness in the digital era. This study aims to comprehensively analyze the role of digital administrative transformation in improving hospital strategic competitiveness through a literature review approach. The method used is a literature review with stages including topic identification, literature search, selection based on inclusion and exclusion criteria, and data analysis and synthesis. The literature search was conducted systematically through academic databases such as Google Scholar and ScienceDirect using relevant keywords. The selected literature was limited to publications within the last 5 years and came from credible scientific sources, such as reputable journals, academic books, and government policy documents. A total of 10 literatures that met the criteria were analyzed using content analysis techniques to identify patterns, themes, and relationships between concepts. The results of the study indicate five main themes, namely: (1) digital transformation as a process of administrative reconstruction based on an integrated system, (2) operational efficiency as the dominant impact of digitalization, (3) data as a basis for strategic decision-making, (4) improving service quality as a representation of hospital competitiveness, and (5) digital transformation as a contextual and non-linear process. In conclusion, digital administrative transformation is a holistic strategy that focuses not only on technology adoption but also encompasses the integration of systems, human resources, and organizational processes to enhance a hospital's strategic competitiveness. Therefore, it is recommended that hospitals strengthen human resource capacity, develop an integrated digital infrastructure, and optimize data utilization in strategic decision-making to support the sustainability of digital transformation.